DETERMINAN PENYALURAN KREDIT UMKM BANK PERSERO - Ashriza Kusuma Wardhana; Augustina Kurniasih (Universitas Mercu Buana, 2018)
ABSTRACT The purpose of this research is to analyze the influence of Third Party Fund (DPK), Capital Adequacy Ratio (CAR) and Non Performing Loan (NPL) to SME Credit Lending at Bank Persero Period Year 2009 - 2015. The method used are descriptive analysis and regression model analysis preceded by the classical assumption test that the data used variables free of problems of normality, multicollinearity, heteroschedasticity, and autocorrelation. The result of the research shows that independent variables simultaneously have an effect on the credit of UMKM. Partially found that DPK, CAR, and NPL have no significant effect on SME credit distribution, the additional variables Yt-1 and Yt+1 are obtained because there are correlation symptoms that show positive and significant influence. This is in line with PBI No. 17/12/PBI/2015 on SME lending, which stipulates that SMEs lending should increase annually as a percentage determined by Bank Indonesia. Keyword : Third Party Fund (DPK), Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), micro (UMKM) credit lending, Goverment owned bank